Trait kepribadian openness to experience dan career exploration pada mahasiswa program studi psikologi Universitas Negeri Semarang - Putri, Citra Pangestika; Muhammad, Amri Hana (Fakultas Psikologi Universitas Hang Tuah, 2024)
Abstract. Career exploration was an individual activity that involved identifying and managing information about careers, aiming to enable individuals to prepare for future careers. One factor that affected career exploration was the openness to experience personality traits. This study aimed to determine the relationship between openness to experience personality trait and career exploration in students of department Psychology of Semarang State University. Research participants were selected using a purposive sampling technique. Data collection in this study used career exploration scale and openness to experience scale. The data analysis employed the product-moment correlation techniques with the assistance of data processing programs. The results of hypothesis testing yielded a correlation coefficient of 0.635 with a significance level of 0.000 (<0.05), indicating a significant positive relationship between the openness to experience personality traits and career exploration in Psychology Study Program students at Semarang State University. This research provided insight into the influence of personality on the career exploration process in career preparation.